Biodiversity of Isolated Cyanobacteria from Desert Soils in Iran. Issue 9 (21st October 2017) - Etemadi-Khah, Atefeh; Pourbabaee, Ahmad Ali; Alikhani, Hossein Ali; Noroozi, Mostafa; Bruno, Laura
ABSTRACT: Cyanobacteria are among the most ubiquitous, ecologically important photo-autotrophs on the Earth. They play important roles in terrestrial environments, especially in arid and semi-arid regions. In this study, the morphological and genetic diversity of the cyanobacteria inhabiting desert soil in Iran were investigated for the first time. The samples were collected at 40 different sites in the Kavir National Park. After cultivation and morphological identification, the 16S rRNA gene was sequenced from the cyanobacterial cultures. Twenty-seven different isolates were genetically and morphologically identified in 23 sites. Morphotypes fitted the description of five genera Phormidium, Trichocoleus, Leptolyngbya, Microcoleus and Tychonema with an abundance of 44.45, 37.04, 11.11, 3.7 and 3.7%, respectively. Sequence comparisons of samples in the National Center for Biotechnology Information (NCBI) and morphological data showed that 48et and 50et strains had 94% similarity to P. animale and 97% similarity to Microcoleus sp., respectively. These strains formed a separate and longer branch in the phylogenetic tree, suggesting relatively distant phylogenetic relationships with other sequences in this study. It seems that these sequences are new strains and other markers are needed for further investigation. Soil analysis showed salinity ranged from 0.23 to 87.8 dS/m and the genus that showed the highest salinity tolerance was Phormidium . The presence of cyanobacterial strains in the Kavir National Park showed that despite the harsh conditions, this place is biologically active.